Strontium magnesium sustained-release apatite bioactive bone cement and its preparation process

By developing strontium magnesium sustained-release apatite bioactive bone cement, the existing calcium phosphate bone cement is solved, and the magnesium ions of magnesium ions are released too quickly are achieved, and bone cement materials with high stability and appropriate degradability have broad clinical application potential.

CN116212117BActive Publication Date: 2025-04-22XI AN JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211715375.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-04-22
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

Existing calcium phosphate bone cement is difficult to degrade in the body, which may trigger an inflammatory response; while the magnesium ions released by magnesium phosphate bone cement is too fast, resulting in a decrease in cement strength and hindering cell vitality.

Method used

A strontium magnesium sustained-release apatite bioactive bone cement was developed, which consists of Ca4(PO4)2O and βCa3-x-ySrxMgy(PO4)2 powders. The amount of strontium doped magnesium is adjustable to the ratio of calcium strontium magnesium/phosphorus, which can slow-release strontium and magnesium ions and has good biodegradation performance.

Benefits of technology

The bone cement has high and long-term stable mechanical properties, appropriate settling time, can adjust the degradation rate, and slow release of strontium magnesium ions that promote bone tissue regeneration, which has significant advantages over traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212117B_ABST
    Figure CN116212117B_ABST
Patent Text Reader

Abstract

The invention discloses a strontium magnesium sustained-release apatite bioactive bone cement and a preparation process thereof. The raw materials include solid phase powder and liquid phase, wherein the solid phase powder includes tetracalcium phosphate powder and beta tricalcium strontium magnesium phosphate powder; wherein the molar ratio of tetracalcium phosphate to beta tricalcium strontium magnesium phosphate is 1:(m+k), m is the ratio of the molar amount of beta tricalcium strontium magnesium phosphate actually participating in the reaction to the molar amount of tetracalcium phosphate, k is the ratio of the molar amount of beta tricalcium strontium magnesium phosphate remaining in the final solidified material after the reaction is completed to the molar amount of tetracalcium phosphate, x is the molar amount of strontium doped in tricalcium phosphate, and y is the molar amount of magnesium doped in tricalcium phosphate; the mass ratio of the solid phase powder to the liquid phase is 1.0-4.0. The strontium magnesium sustained-release apatite bioactive bone cement of the invention is only composed of two-phase powders, the amount of strontium magnesium doped and the calcium strontium magnesium / phosphorus ratio are adjustable, and it can sustainably release special pharmacological strontium and magnesium ions without toxic side effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical cement, and in particular relates to strontium magnesium slow-release apatite bioactive bone cement and a preparation process thereof. Background Art

[0002] Hydroxyapatite (HA) is one of the most commonly used calcium phosphates in bone tissue engineering. Artificial bone grafts composed of synthetic HA have been widely used as biomaterials. Calcium phosphate cement (CPC) has a porous structure and its solidified product is hydroxyapatite. However, this artificially synthesized hydroxyapatite is difficult to degrade in the body, and this residue becomes a hidden danger of inducing inflammatory response. Therefore, it is very important to develop calcium phosphate cement with certain biodegradability.

[0003] Compared with traditional calcium phosphate bone cement, the solubility of magnesium phosphate bone cement is much higher than calcium phosphate, so it releases magnesium ions faster in the body. On the one hand, this causes the strength of the cement to drop rapidly, and on the other hand, excessively high concentrations of magnesium ions will significantly hinder cell vitality, and it still cannot be used as a biomaterial. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a strontium magnesium sustained-release apatite bioactive bone cement and a preparation process thereof. The strontium magnesium sustained-release apatite bioactive bone cement of the present invention is composed of only two-phase powder, the amount of strontium and magnesium added and the calcium strontium magnesium / phosphorus ratio are adjustable, the degradation rate is controllable, and special pharmacological strontium and magnesium ions can be sustained-released without toxic side effects.

[0005] The technical solution adopted by the present invention is as follows:

[0006] Strontium magnesium sustained-release apatite bioactive bone cement, the raw materials of which include solid phase powder and liquid phase, the solid phase powder includes Ca4(PO4)2O powder and βCa 3-x-y Sr x Mg y (PO4)2 powder;

[0007] Among them, Ca4(PO4)2O powder and βCa 3-x-y Sr x Mg y The molar ratio of (PO4)2 powder is 1:(m+k), where m is the βCa actually involved in the reaction. 3-x-y Sr x Mg y The ratio of the molar amount of (PO4)2 to the molar amount of Ca4(PO4)2O, k is the βCa remaining in the final solid after the reaction is completed. 3-x-y Sr x Mg yThe ratio of the molar amount of (PO4)2 to the molar amount of Ca4(PO4)2O, where x is the molar amount of strontium doped in tricalcium phosphate and y is the molar amount of magnesium doped in tricalcium phosphate;

[0008] The mass ratio of the solid-phase powder to the liquid phase is 1.0 to 4.0.

[0009] Preferably, the particle size range of the Ca4(PO4)2O powder is 0.8 μm to 200 μm.

[0010] Preferably, βCa 3-x-y Sr x Mg y (PO4)2 powder has a particle size range of 0.8 to 200 μm.

[0011] Preferably, 0 < m < 50, 0 < k < 50, 0 < x ≤ 3.0, 0 < y ≤ 3.0.

[0012] Preferably, the liquid phase uses a dilute phosphoric acid aqueous solution or deionized water.

[0013] Preferably, the concentration w of phosphoric acid in the dilute phosphoric acid aqueous solution satisfies 0 mol / L < w ≤ 2.0 mol / L.

[0014] Preferably, the composition of the strontium-magnesium slow-release apatite bioactive bone cement includes strontium-magnesium-doped hydroxyapatite Ca 10-p-s-q Sr p Mg s (PO4)6(OH) 2-2q and βCa 3-x-y Sr x Mg y (PO4)2, where p, s, q satisfy the following conditions: p = mx / n, s = my / n, q = 10-(4 + 3m) / n, n = 0.333(m + 1)+(0.069 + 0.052m)w / z, 0 < p + s ≤ 10, 0 ≤ q ≤ 1, w is the concentration of dilute phosphoric acid, and z is the mass ratio of the solid-phase powder to the liquid phase.

[0015] Preferably, strontium-magnesium-doped hydroxyapatite Ca 10-p-s-q Sr p Mg s (PO4)6(OH) 2-2q and βCa 3-x-y Sr x Mg yThe mass percentages of (PO4)2 are [100na / (na+kb)]% and [100kb / (na+kb)]% respectively, where a and b are intermediate parameters, a=87.62x+24.31y+1004.69-40.083(p+s)-74.082q, b=47.54x-15.77y+310.2.

[0016] Preferably, the strontium magnesium sustained-release apatite bioactive bone cement solidified body has a compressive strength of 15 to 50 MPa, an initial setting time of 3 to 8 min, a final setting time of 9 to 15 min, and a calcium strontium magnesium / phosphorus ratio of 1.50 to 1.67.

[0017] The preparation method of the strontium magnesium sustained-release apatite bioactive bone cement of the present invention comprises the following steps:

[0018] The solid phase powder is blended with the liquid phase to prepare the strontium magnesium sustained-release apatite bioactive bone cement.

[0019] The present invention has the following beneficial effects:

[0020] The strontium magnesium sustained-release apatite bioactive bone cement of the present invention is a degradable strontium magnesium-doped biphasic calcium phosphate bioactive bone cement, and its biodegradation rate can not only be regulated according to the parameters such as the relative content of the two phases in the solidified product, the amount of strontium / magnesium, and the molar ratio of strontium magnesium / phosphorus, but also is higher than the degradation rate of single-phase strontium-doped apatite bone cement. The strontium magnesium-doped apatite bioactive bone cement of the present invention has high and long-term stable mechanical properties, suitable setting time, adjustable strontium / magnesium content and calcium strontium magnesium / phosphorus ratio, controllable degradation rate, and can slowly release strontium magnesium ions that promote bone tissue regeneration. Compared with pure magnesium phosphate bone cement, it has more long-term stable mechanical properties and appropriate magnesium ion sustained release rate. This material has significant advantages over traditional calcium phosphate bone cement and other types of strontium-doped or magnesium-doped calcium phosphate bone cements, and is expected to be more widely used in clinical practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 SEM photo of the fracture morphology of the sample in Example 1 of the present invention after being crushed;

[0022] Figure 2 XRD spectrum of the sample after curing in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0024] The strontium-magnesium slow-release apatite bioactive bone cement of the present invention is composed of two-phase powders, and is a preparation process of a novel strontium-magnesium co-doped apatite bone repair material with adjustable strontium / magnesium doping amount and calcium-strontium-magnesium / phosphorus ratio, capable of slowly releasing special pharmacological strontium element and magnesium element and being biodegradable.

[0025] Specifically, the preparation method of the strontium-magnesium slow-release apatite bioactive bone cement of the present invention is as follows:

[0026] 1) Composition of solid-phase powder: Mix tetracalcium phosphate Ca4(PO4)2O and β-tricalcium phosphate strontium magnesium βCa 3-x-y Sr x Mg y (PO4)2 powders in a molar ratio of 1:(m + k), where m is the molar ratio of βCa 3-x-y Sr x Mg y (PO4)2 actually participating in the reaction in the reactants to the molar amount of Ca4(PO4)2O, and k is the molar ratio of the remaining βCa 3-x-y Sr x Mg y (PO4)2 to the molar amount of Ca4(PO4)2O in the final cured product, with 0 < x ≤ 3.0, 0 < y ≤ 3.0, 0 < m < 50, 0 < k < 50;

[0027] 2) Preparation of liquid phase: Prepare a dilute phosphoric acid H3PO4 aqueous solution with a concentration of w or use deionized water as the cement curing liquid, where 0 mol / L ≤ w ≤ 2.0 mol / L;

[0028] 3) Selection of solid / liquid ratio: The mass ratio of the solid-phase powder to the liquid phase during mixing is z, where 1.0 ≤ z ≤ 4.0.

[0029] Harmonize the solid-phase powder and the liquid phase according to the above solid / liquid ratio range to prepare the strontium-magnesium slow-release apatite bioactive bone cement of the present invention.

[0030] The new strontium-magnesium slow-release apatite bioactive bone cement prepared by the preparation process of the present invention has a final cured product of strontium-magnesium-doped hydroxyapatite Ca 10-p-s-q Sr p Mg s (PO4)6(OH) 2-2q and the remaining β-tricalcium phosphate strontium magnesium βCa 3-x-y Sr x Mg y (PO4)2, where p, s, q satisfy p = mx / n, s = my / n, q = 10 - (4 + 3m) / n, n = 0.333(m + 1) + (0.069 + 0.052m)w / z, 0 < p + s ≤ 10, 0 ≤ q ≤ 1, etc.; x, y are the same as βCa 3-x-y Srx Mg y In the (PO4)2 molecular formula, x, y, and w are the concentrations of dilute phosphoric acid, z is the mass ratio of the solid phase powder to the liquid phase, m and k have the same physical meanings as above, and n, p, and q are intermediate parameters for easy expression; Ca in the solidified product 10-p-s-q Sr p Mg s (PO4)6(OH) 2-2q With βCa 3-x-y Sr x Mg y The mass percentages of (PO4)2 are [100na / (na+kb)]% and [100kb / (na+kb)]%, respectively, where a and b are only intermediate parameters, a=87.62x+24.31y+1004.69-40.083(p+s)-74.082q, b=47.54x-15.77y+310.2. As long as the parameters x, y, s, w, z, m, and k are given, n, p, s, and q can be calculated to determine the specific molecular formula of strontium-doped magnesium hydroxyapatite, the amount of strontium / magnesium doped, and the calcium-strontium-magnesium-phosphorus ratio.

[0031] The novel strontium-magnesium-apatite bioactive bone cement prepared by the preparation process of the present invention has a solidified body compression strength of 15-50 MPa, an initial setting time of 3-8 min, a final setting time of 9-15 min, a strontium / magnesium content of 0%-99%, and a calcium-strontium-magnesium / phosphorus ratio of 1.50-1.67, and is suitable for the repair and regeneration of bones in non-load-bearing parts of the human body.

[0032] The novel strontium-magnesium-apatite bioactive bone cement prepared by the preparation process of the present invention comprises solid phase powders of tetracalcium phosphate Ca4(PO4)2O, tricalcium strontium magnesium β Ca 3-x-y Sr x Mg y The average particle size ranges of (PO4)2 are 0.8μm~200μm and 0.8~200μm respectively.

[0033] Example 1

[0034] 0.6g cement mixed powder (Ca4(PO4)2O and βCa 2.5 Sr 0.25 Mg 0.25The slurry was mixed with 0.33 g H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z=1.8:1) and 0.75 mol / L (PO4)2 (m=2+0.5), and 0.33 g H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z=1.8:1) with a spoon for 30 seconds to form a uniform cement slurry, which was filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted with a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in simulated body fluid (SBF). After 3 days, the final product composition of the solidified body was 86.35% of strontium-doped magnesium hydroxyapatite (Ca 8.56 Sr 0.48 Mg 0.48 (PO4)6(OH) 1.02 , (Ca+Sr+Mg) / P=1.59, Sr / (Ca+Sr+Mg)=5.04%, Mg / (Ca+Sr+Mg)=5.04%) and 13.65% β Ca 2.5 Sr 0.25 Mg 0.25 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 25.90MPa. The initial setting time is 5min and the final setting time is 11.5min. Figure 1 From the scanning electron microscope photo of the fracture of the solidified product, it can be seen that there are particles of similar size and needle-shaped crystals attached to the surface. Figure 2 The XRD spectrum analysis shows that the solidified product is a two-phase mixture of hydroxyapatite and tricalcium phosphate. Figure 1 The needle-shaped crystals are hydroxyapatite Ca in the reaction product. 8.56 Sr 0.48 Mg 0.48 (PO4)6(OH) 1.02 Crystals, particles are the remaining unreacted βCa 2.5 Sr 0.25 Mg 0.25 (PO4)2.

[0035] Example 2

[0036] 0.6g cement mixed powder (Ca4(PO4)2O and βCa 2.5 Sr 0.25 Mg 0.25The slurry was mixed with 0.33 g H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z=1.8:1) and 0.75 mol / L (PO4)2 (m=2, k=1) for 30 seconds with a spoon to form a uniform cement slurry, which was then filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted with a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in SBF simulated body fluid. After 3 days, the final product of the solidified body was 75.98% strontium-doped magnesium hydroxyapatite (Ca 8.56 Sr 0.48 Mg 0.48 (PO4)6(OH) 1.02 , (Ca+Sr+Mg) / P=1.59, Sr / (Ca+Sr+Mg)=5.04%, Mg / (Ca+Sr+Mg)=5.04%) and 24.02% βCa 2.5 Sr 0.25 Mg 0.25 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 18.94MPa. The initial setting time is 6min and the final setting time is 13.5min.

[0037] Example 3

[0038] 0.6 g cement mixed powder (Ca4(PO4)2O and β Ca 2.5 Sr 0.1 Mg 0.4 The slurry was mixed with 0.33 g H3PO4 aqueous solution (x=0.1, y=0.4; solid / liquid mass ratio z=1.8:1) and 0.75 mol / L (PO4)2 (m=2+0.5), and 0.33 g H3PO4 aqueous solution (x=0.1, y=0.4; solid / liquid mass ratio z=1.8:1) with a spoon for 30 seconds to form a uniform cement slurry, which was filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted with a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in SBF simulated body fluid. After 3 days, the final product of the solidified body was 76.47% strontium-doped magnesium hydroxyapatite (Ca 8.39 Sr 0.19 Mg 0.75 (PO4)6(OH) 0.66, (Ca+Sr+Mg) / P=1.56, Sr / (Ca+Sr+Mg)=2.04%, Mg / (Ca+Sr+Mg)=8.15%) and 23.52% βCa 2.5 Sr 0.1 Mg 0.4 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 19.36MPa. The initial setting time is 5.5min and the final setting time is 13.5min.

[0039] Example 4

[0040] 0.6g cement mixed powder (Ca4(PO4)2O and βCa 2.5 Sr 0.25 Mg 0.25 The slurry was mixed with 0.33 g of 1.0 mol / L H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z was 1.8:1) using a spoon for 30 seconds to form a uniform cement slurry, which was then filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted under a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in SBF simulated body fluid. After 3 days, the final product of the solidified body was 86.50% of strontium-doped magnesium hydroxyapatite (Ca 8.2 Sr 0.46 Mg 0.46 (PO4)6(OH) 0.24 , (Ca+Sr+Mg) / P=1.52, Sr / (Ca+Sr+Mg)=5.04%, Mg / (Ca+Sr+Mg)=5.04%) and 13.50% β-Ca 2.5 Sr 0.1 Mg 0.4 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 27.43MPa. The initial setting time is 4.5min and the final setting time is 11.5min.

[0041] Example 5

[0042] 0.6 g cement mixed powder (Ca4(PO4)2O and β Ca 2.5 Sr 0.4 Mg 0.1The slurry was mixed with 0.30 g of H3PO4 aqueous solution (x=0.40, y=0.10; solid / liquid mass ratio z=2.0:1) with a spoon for 30 seconds to form a uniform cement slurry, which was then filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted with a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in SBF simulated body fluid. After 3 days, the product composition of the solidified body was 85.55% of strontium-doped magnesium hydroxyapatite (Ca 8.45 Sr 0.75 Mg 0.19 (PO4)6(OH) 0.78 , (Ca+Sr+Mg) / P=1.57, Sr / (Ca+Sr+Mg)=7.98%, Mg / (Ca+Sr+Mg)=2.02%) and 14.45% βCa 2.5 Sr 0.1 Mg 0.4 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 25.57MPa. The initial setting time is 6.5min and the final setting time is 14.5min.

[0043] Example 6

[0044] 0.6g cement mixed powder (Ca4(PO4)2O and βCa 2.5 Sr 0.25 Mg 0.25 The slurry was mixed with 0.33 g H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z was 1.8:1) and 0.75 mol / L (PO4)2 (m=2+2), i.e. m=2, k=2) using a medicine spoon for 30 seconds to form a uniform cement slurry, which was then filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted under a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in SBF simulated body fluid. After 3 days, the product composition of the solidified body was 61.43% of strontium-doped magnesium hydroxyapatite (Ca 8.39 Sr 0.47 Mg 0.47 (PO4)6(OH) 0.66, (Ca+Sr+Mg) / P=1.56, Sr / (Ca+Sr+Mg)=5.19%, Mg / (Ca+Sr+Mg)=5.19%) and 38.57% βCa 2.5 Sr 0.25 Mg 0.25 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 15.49MPa. The initial setting time is 5.5min and the final setting time is 13.5min.

[0045] Example 7

[0046] 0.6g cement mixed powder (Ca4(PO4)2O and βCa 2.5 Sr 0.25 Mg 0.25 The slurry was mixed with 0.33 g H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z=1.8:1) and 0.75 mol / L (PO4)2 (m=2+1.5), and 0.33 g H3PO4 aqueous solution (x=0.25, y=0.25; solid / liquid mass ratio z=1.8:1) with a spoon for 30 seconds to form a uniform cement slurry, which was filled into a stainless steel cylindrical mold with a diameter of 6 mm and a height of 12 mm and compacted with a pressure of 0.7 MPa. The cylindrical sample was inserted into a glass tube with a diameter of 6.5 mm and a height of 13 mm, and then placed in an environment with a temperature of 37°C and a relative humidity of 100% for curing. After pre-curing for 30 minutes, the sample was taken out and quickly immersed in SBF simulated body fluid. After 3 days, the product composition of the solidified body was 67.97% of strontium-doped magnesium hydroxyapatite (Ca 8.39 Sr 0.47 Mg 0.47 (PO4)6(OH) 0.66 , (Ca+Sr+Mg) / P=1.56, Sr / (Ca+Sr+Mg)=5.19%, Mg / (Ca+Sr+Mg)=5.19%) and 32.03% βCa 2.5 Sr 0.25 Mg 0.25 (PO4)2. The average compressive strength of the sample after immersion in SBF for 3 days is 18.45MPa. The initial setting time is 5.5min and the final setting time is 12.5min.

[0047] According to the above example, the compressive strength of the strontium-magnesium co-doped biphasic calcium phosphate bone cement solidified body is 15-50 MPa, the initial setting time is 3-8 min, the final setting time is 9-15 min, and the calcium-strontium-magnesium / phosphorus ratio is 1.50-1.67, which is suitable for the repair and regeneration of bones in non-load-bearing parts of the human body.

[0048] As can be seen from the above scheme, the present invention reduces the complex ion-doped bone cement raw materials to two types through the solid phase sintering method, making the raw material system simpler. In addition, the present invention transfers magnesium ions from the pure magnesium phosphate bone cement system to the strontium-doped biphasic calcium phosphate bone cement system, while retaining its biological properties, overcoming the disadvantage of magnesium phosphate bone cement degrading too quickly. Finally, the present invention utilizes the higher degradability of strontium-doped biphasic calcium phosphate bone cement to maintain the strength and certain degradability of cement, which will have a wider clinical application space and broader industrialization prospects.

Claims

1. Strontium magnesium sustained-release apatite bioactive bone cement, characterized in that: The raw materials include solid phase powder and liquid phase, wherein the solid phase powder includes Ca4(PO4)2O powder and βCa 3-x-y Sr x Mg y (PO4)2 powder; Among them, Ca4(PO4)2O powder and βCa 3-x-y Sr x Mg y The molar ratio of (PO4)2 powder is 1:(m+k), where m is the βCa actually involved in the reaction. 3-x-y Sr x Mg y The ratio of the molar amount of (PO4)2 to the molar amount of Ca4(PO4)2O, k is the βCa remaining in the final solid after the reaction is completed. 3-x-y Sr x Mg y The ratio of the molar amount of (PO4)2 to the molar amount of Ca4(PO4)2O, x is the molar amount of strontium doped in tricalcium phosphate, and y is the molar amount of magnesium doped in tricalcium phosphate; The mass ratio of solid phase powder to liquid phase is 1.0 to 4.

0.

2. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 1, characterized in that: The particle size range of Ca4(PO4)2O powder is 0.8μm to 200μm.

3. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 1, characterized in that: βCa 3-x-y Sr x Mg y The particle size range of (PO4)2 powder is 0.8~200μm.

4. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 1, characterized in that: 0 <m<50,0<k<50,0<x≤3.0,0<y≤3.0。 5. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 1, characterized in that: The liquid phase is a dilute phosphoric acid aqueous solution or deionized water.

6. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 5, characterized in that: The concentration w of phosphoric acid in dilute phosphoric acid aqueous solution satisfies 0 mol / L <w≤2.0mol / L。 7. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 5, characterized in that: The components of the strontium and magnesium slow-release bioactive bone cement include strontium- and magnesium-doped hydroxyapatite Ca 10-p-s-q Sr p Mg s (PO4)6(OH) 2-2q and βCa 3-x-y Sr x Mg y (PO4)2, where p, s, and q satisfy the following conditions: p = mx / n, s = my / n, q = 10-(4 + 3m) / n, n = 0.333(m + 1)+(0.069 + 0.052m)w / z, 0 < p + s ≤ 10, 0 ≤ q ≤ 1, w is the concentration of dilute phosphoric acid, and z is the mass ratio of the solid-phase powder to the liquid phase.

8. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 7, characterized in that: Sr-doped Mg-hydroxyapatite Ca 10-p-s-q Sr p Mg s (PO4)6(OH) 2-2q With βCa 3-x-y Sr x Mg y The mass percentages of (PO4)2 are [100na / (na+kb)]% and [100kb / (na+kb)]% respectively, where a and b are intermediate parameters, a=87.62x+24.31y+1004.69-40.083(p+s)-74.082q, b=47.54x-15.77y+310.

2.

9. The strontium magnesium sustained-release apatite bioactive bone cement according to claim 1, characterized in that: The strontium magnesium sustained-release apatite bioactive bone cement solidified body has a compression strength of 15-50 MPa, an initial setting time of 3-8 minutes, a final setting time of 9-15 minutes, and a calcium strontium magnesium / phosphorus ratio of 1.50-1.

67.

10. The method for preparing the strontium magnesium sustained-release apatite bioactive bone cement according to claim 1, characterized in that: The process includes the following: The solid phase powder is blended with the liquid phase to prepare the strontium magnesium sustained-release apatite bioactive bone cement.

Citation Information

Patent Citations

  • Strontium ion-mediated self-curing calcium phosphate bone cement

    CN109381740A

  • Magnesium strontium-calcium phosphate / calcium silicate composite bone cement filler as well as preparation and application thereof

    CN111773434A